STRATEGI KOMUNIKASI MALU DONG COMMUNITY DALAM MENGEDUKASI MASYARAKAT UNTUK PEDULI TERHADAP KEBERSIHAN LINGKUNGAN - Sanjiwani, I.A Agung Anindia; Pascarani, Ni Nyoman Dewi; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT The growth of population and the lack of awareness of the public to keep the environment have a direct impact on increasing the volume of garbage and sewage in the city of Denpasar. Production of garbage in the city of Denpasar has increased each year, from 2016 the volume of a garbage reached 850 tons in day and 900 tons in 2017. Malu Dong Community moved to eradicate such phenomena and do a communication strategy. This research aims to provide an overview and explanation of the related communication strategy undertaken by the MDC in educating the public to care about the cleanliness of the environment. The object of this research is Malu Dong Community. type of this research is a descriptive qualitative data collection techniques form of interviews, observation, and document Studies. The results of this research are as follows, MDC are educating their audience by collecting litters in the middle of crowds and targeting each of their audience with different approach, and also they are utilizing outdoor media, for example, flags in order to properly deliver a message to their target audiences. Keywords: Campaign, Communication Strategy, Garbage, Malu Dong Community